Guanine storage vacuoles sequester guanine crystals and serve as nitrogen reserves in Chlamydomonas reinhardtii - Ursula Goodenough; Robyn Roth; Jae-Hyeok Lee (Proceedings of the National Academy of Sciences, 2025)
Nitrogen cycles in Chlamydomonas reinhardtii have historically been studied in the context of exogenous ammonium/nitrate availability and uptake. Recently, crystalline guanine has been identified, using Raman microscopy, in the cytoplasm of numerous microalgae, including C. reinhardtii . The signal level is influenced by availability of exogenous nitrogen, suggesting that the deposits serve as a nitrogen store. We report the visualization of these guanine crystals in C. reinhardtii and other microalgae using quick-freeze deep-etch electron microscopy. They prove to reside within cytoplasmic vacuoles: A membrane with a high density of small intramembranous particles surrounds a uniform, coarsely granular interior matrix within which stacks of flat crystals assemble, often in stunning abundance. We designate these as guanine storage vacuoles (GSVs). In C. reinhardtii and other members of the Chlamydomonadales, a discrete disc-shaped granular domain occupies the center of each GSV, and the crystals arise within or at the edges of this domain, suggesting that it represents an amorphous form of guanine. In C. reinhardtii , GSVs are numerous in log-phase cells, are not found in cells maintained in nitrogen-free medium, and reappear within 8 h after the cells are provided with nitrogen, initially as small disc-containing vacuoles. We compare this cycle with that of the polyphosphate granules localized in acidocalcisomes. Nineteen enzyme families and 10 transporters are predicted to participate in guanine-related pathways in C. reinhardtii , many showing strong upregulation with nitrogen starvation. These understandings will inform future studies on the contributions made by GSVs to the metabolism and physiology of eukaryotic microalga.